Plasticity of sorghum kernel weight to increased assimilate availability - Gambin, Brenda Laura (2007)
Understanding source or sink limitations on crop yield is critical for the rational design of agricultural practices as well as breeding strategies. In the present article, we studied sorghum [Sorghum bicolor (L.) Moench] source-sink yield limitations during grain filling, and tested the hypothesis that the time in which kernel maximum water content is reached during grain filling defines a temporal limit for the crop to profit from source increases. Earlier studies have never tested increasing assimilate availability per kernel in different developmental stages. We conducted a field experiment increasing assimilate availability per kernel at anthesis and 15 days after anthesis in commercial hybrids. The anthesis treatment was aimed to increase assimilates per kernel from early grain filling, and the 15 days after anthesis treatment from the stage kernel maximum water content was achieved. Both treatments removed 50% of the kernels from one side of the panicle. Kernel dry weight (KW), kernel water content and kernel volume were measured in apical and basal positions of the panicle throughout grain filling. Increased assimilate availability always yielded a higher KW (∼34% increase). This KW increase was consistent across the two kernel developmental stages when the treatment was imposed, the panicle position and hybrid. Achieving maximum water content did not prevent kernels from increasing their weight when assimilates were subsequently increased. Final KW was closely related to maximum kernel volume (r2 = 0.72; n = 42; p < 0.0001). Increased assimilate availability per kernel promoted changes in both kernel growth rate and duration of grain filling. We applied a quantitative approach for determining the magnitude of sorghum KW changes in response to assimilate availability changes during grain filling. This allowed us to compare our data to previously published articles, and to determine any general response pattern across environments. The analysis supported our observation that sorghum KW is highly responsive to increased assimilates, and indicated that increased assimilate availability during filling always increased sorghum KW. As such, growth of sorghum kernels is predominately source limited; breeding and management practices aimed to increase assimilate availability per kernel will be likely to enhance sorghum yield. Results show that the crop has the capacity to profit from source increases even after the initial grain-filling stages have occurred. © 2006 Elsevier B.V. All rights reserved.